Inherently anti-metastatic peptide hydrogels for sonodynamic-amplified ferroptosis in cancer therapy - Hongxia Zhang; Yamei Wang; Mengmeng Jiang; Kunyu Wang; Jingru Yan; Gongyu Li; Zhen Zheng (Materials Today Bio, 2025)
Cancer metastasis remains a significant challenge in oncology, prompting the exploration of innovative biomaterials to enhance treatment efficacy. While many hydrogels only serve as passive carriers, this study presents two novel self-assembling peptides, CWEWTWY and NapFFSGP, which form supramolecular hydrogels with intrinsic anti-metastatic properties. We demonstrate a correlation between the nanofibrous morphology of these peptides and their enhanced anti-metastatic activity, mediated by disruption of F-actin organization and impacting pathways related to cancer cell adhesion and actin filament dynamics. In vivo studies confirm a significant reduction in lung metastasis using a 4T1 pulmonary metastasis model. We also demonstrate their potential as a simple, synergistic platform integrating sonodynamic therapy (SDT) and ferroptosis. Ironporphyrin (FP), incorporated into Gel@FP, acts as both a sonosensitizer and ferroptosis inducer. Upon ultrasound irradiation, FP generates localized reactive oxygen species, further amplifying ferroptosis through enhanced lipid peroxidation. Gel@FP combined with ultrasound demonstrates potent antitumor efficacy in vitro and in vivo, promoting apoptosis, ferroptosis, and immunogenic cell death, leading to enhanced tumor regression and robust immune activation. Our findings highlight the potential of anti-metastatic hydrogels as a promising multifunctional platform to address the challenges of metastasis while enhancing antitumor immunity.